734 PL11.06 PROGNOSTIC FACTORS FOR MORTALITY IN PATIENTS WITH ANASTOMOTIC LEAKAGE AFTER ESOPHAGECTOMY FOR CANCER (TENTACLE—ESOPHAGUS STUDY). (17th September 2021) - Ubels, Sander; Verstegen, Moniek; Bouwense, Stefan; Hannink, Gerjon; Klarenbeek, Bastiaan; Siersema, Peter; Workum, Frans; Rosman, Camiel
Abstract: : Anastomotic leakage (AL) is a common and potentially life-threatening complication after esophagectomy. In patients with AL it is largely unknown which patient parameters and leakage characteristics are associated with leak severity and mortality. We aimed to identify prognostic factors for mortality in patients with anastomotic leakage after esophagectomy. Methods: The TENTACLE—Esophagus study is an international retrospective cohort study, in which 1451 patients with AL after esophagectomy between 2011 and 2019 were included in 71 centers from 20 countries. Potential prognostic factors were selected from literature and a hypothetical association with mortality. Confounders of (individual) prognostic factors were identified using a directed acyclic graph approach to minimize bias. Primary outcome was 90-day mortality. Logistic regression analysis was performed to estimate crude and adjusted odds ratios (AOR) and 95% confidence intervals (95%CI). The study protocol is accessible at www.tentaclestudy.com . Results: Overall 90-day mortality rate was 11.6%. Leakage characteristics with the largest prognostic effect on mortality were gastric conduit ischemia/necrosis (AOR 2.23, 95%CI 1.43-3.49), defect circumference ≥ 25% (AOR 2.10, 95%CI 1.32-3.36) and intrathoracic fluid collections (drained AOR 1.98, 95%CI 1.05-3.75; undrained AOR 2.43, 95%CI 1.57-3.75). Patient parameters with the largest prognostic effect were ASA-score ≥ 3 (AOR 4.18, 95%CI 1.67-10.51), ECOG-score ≥ 2 (AOR 2.83, 95%CI 1.56-5.14) and respiratory failure (AOR 3.89, 95%CI 2.67-5.66), hemodynamic failure (AOR 3.09, 95%CI 1.96-4.88) or renal failure (AOR 4.08, 95%CI 2.20-7.59) at time of AL diagnosis. Conclusion: Defect circumference, intrathoracic fluid collections, gastric conduit condition and several patient parameters were identified as prognostic factors for mortality in patients with AL. Adjusting for these prognostic factors may reduce confounding bias in future studies assessing efficacy of AL treatments. The identified prognostic factors contribute to the understanding of the severity of anastomotic leakage after esophagectomy and may be used to recognize the severity of an anastomotic leak in individual patients.